Ugandan Men Exposed to Intimate Partner Violence: A Cross-Sectional Survey of Nationally Representative Data - Waila Jacinta; Lule Herman; Wilson Lowery Michael; Bärnighausen Till; Abio Anne (United States, 2022)
Although women typically constitute the largest proportion of the population who experience the deleterious effects of intimate partner violence (IPV), understanding the bidirectional nature of IPV is important for developing nuanced prevention initiatives. This study examines data from the 2016 Ugandan Demographic and Health Survey. Participants were selected from households in all the 15 regions in Uganda using a two stage sampling design. A total of 2858 men who were in a heterosexual union or separated/divorced were included in the analysis. Univariate and multivariable logistic regression analyses were performed with the aim of identifying associations between selected demographic variables and male exposure to all forms of IPV combined, psychological violence, physical violence and sexual violence. The prevalence of lifetime IPV and during the 12 months preceeding the survey respectively was 43.6 and 30.5% in all forms, with 35.9 and 24.8% reporting psychological, 20.2 and 11.9% for physical and 8.2 and 5.7% sexual violence. The key factors associated with all forms of IPV were being afraid of their wife/partner most of the time (OR = 5.10, 95% CI 2.91, 8.96) controlling behaviour of the intimate partner (OR = 3.80, 95% CI 2.84, 5.07), bi-directional violence against the partner (OR = 3.20, 95% CI 2.49, 4.12), alcohol consumption by the intimate partner (OR = 1.85, 95% CI 1.40, 2.45). The factors associated with males who experience IPV appear to be modifiable and may warrant consideration for inclusion in programs supporting both males and females who experience IPV.